The Effect of the Teacher Pedagogic Competency and Teacher Work Motivation of the Student Learning of the Outcomes - Marheni, Desi; Fitria, Happy; Puspita, Yenny (Jurnal Pendidikan Tambusai, 2021)
The aim of this study is to describe the effect of teacher pedagogical competence and the motivation of teachers to work partially or collectively on the learning outcomes of SMA Negeri in the OKU Selatan District. This research is based on quantitative methods. The research population consisted of all State Senior High School teachers in South OKU Regency, with a total of 703 staff. The sample was collected using arandom sampling technique of 137 respondents. Data was analyzed using multiple linear regression, partial correlation and multiple correlation. This study led to the conclusion (1) that teaching competence has an effect on the student learning outcomes of SMA Negeri in OKU Selatan Regency. (2) The effect of teacher motivation on student learning outcomes of SMA Negeri in OKU Selatan Regency (3) is the effect of teacher pedagogical competence and motivation The work of teachers together on learning outcomes of SMA Negeri in OKU Selatan Regency means that learning outcomes SMA Negeri in OKU Selatan Regency can be improved by improving and increasing the quality of teaching competence and motivation of teaching staff.